Education and lifestyle in spaces symbolic reproduction - Padilla Loredo, Silvia (Libros UAT, 2018)
Attending to the design of the generation of healthy communities and education for health means emphasizing that the benefits of scientific and technological progress are really at the service of humanity; that public policies are assumed from the design, application and monitoring with criteria of equity and social justice, that counteract the harmful effects of neoliberalism. Because the appearance of chronic degenerative diseases derived from the modification of diet and lifestyle are effects of the policy applied under the dictates of the international market. The advantages of a globalized world have not been demonstrated, because in the humanistic field it is demonstrating an enormous failure to achieve the development of humanity, not only because of the poor nutrition of the populations, but also because of malnutrition and the reappearance of diseases that were considered extinct as dengue, malaria, smallpox or measles, to name a few. The migration of large population centers carries with it physical strengths and weaknesses, typical of an immunological system typical of their communities and territory of origin. The spread of new diseases and the coexistence of previously acquired diseases causes epidemics to become pandemics. In the international context, the expansionist demands of transnational corporations have established pressures that affect the health of nations. Pharmaceutical consortiums benefit from treating the disease. It is essential to close ranks for the health care of the population, so that it does not require medication, rather, it encourages the development of a healthy life. In this task, the family, the community and society as a whole should combine efforts to guarantee health, the participation of the State is fundamental for the redistribution of the benefits of the wealth generated in each country, for the satisfaction of needs basic of the inhabitants. The best way to fight the disease is to avoid its appearance, hence the need for prevention and education that makes possible the harmonious development of society.